EROPANISASI KEBIJAKAN IMIGRASI DAN POLITISASI KEAMANAN IMIGRAN DI NEGARA-NEGARA VISEGRAD - Sugito Sugito (Intermestic: Journal of International Studies, 2021)
The wave of migration that hit the European Union since 2015 had a political and security impact on both EU institutions and its member states. The policy of sharing responsibility or immigrant quotas did not get agreement from the Visegrad countries. Several previous studies that used a constructivist approach explained that the rejection occurred due to the securitization of immigrants in each country. This article seeks to understand the resistance of the Visegrad states from a critical perspective by using the concept of politicization of security. The research method used is qualitative with an analysis of existing data in online news media, European Union documents, and scientific journals. The article found that the politicization of security toward immigrants in each Visegrad country happened on public discourse and political campaigns by government elites and political parties. The purpose of this security politicization was to perpetuate power relations.